(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2026)
The fatty liver disease (FLD) among children is increasingly being accepted as a severe comorbidity, which is often linked with metabolic and endocrine pathologies. The aim of the research was to characterize the clinical prognosis of a child group of patients with FLD and, more precisely, to evaluate the correlations between the metabolic control, liver injury biomarkers, and non-invasive fibrosis index. The study was performed as a cross-sectional study involving 39 children with FLD. The data obtained were demographic, comorbidity, primary diagnosis, and significant laboratory parameters (platelets, ALT, AST, and HbA1c). Also established was the AST to Platelet Ratio Index (APRI) as a non-invasive method for assessing hepatic fibrosis. In order to characterize data statistically, the descriptive statistics and Pearson correlation coefficients were employed to estimate the relationship among the clinical variables (age, BMI, laboratory values, and APRI scores). The comorbidity burden was also high (46.2 with diabetes being the most common and 41.0 with hypertension being the next most common). The most common first disease diagnosis was T1DM (53.8%). Lab data showed a median of 20 U/L of ALT and 21 U/L of AST, and AST has a great outlier skewness (1011.7 U/L). Mean haemoglobin was 9.08 (±3.61), and mean APRI was 0.32 (±0.45). Correlation analysis showed that there was a close correlation between ALT and APRI (r = 0.86). On the contrary, both ALT and APRI had linear relationships with HbA1c. Pediatric FLD in this group is mostly manifested in T1DM and major metabolic comorbidity. Liver injury severity and predicted risk of fibrosis occurrences, which are vigorously correlated with transaminase levels, do not seem to be closely associated with short-term glycemic regulation, assessed by HbA1c. These results indicate that FLD in children has a multifactorial etiology, and therefore, management should be more extensive than glycemic control, as it should involve overall metabolic and hepatic monitoring.